Unprecedented outbreak of respiratory syncytial virus in Taiwan associated with ON1 variant emergence between 2010 and 2020. Issue 1 (31st December 2022) - Lin, Wei-Hsuan; Wu, Fang-Tzy; Chen, Yi-Yin; Wang, Chih-Wei; Lin, Ho-Chen; Kuo, Ching-Chia; Lai, Wan-Chun; Lin, Fang-Ju; Tiew, Wan-Tin; Tsai, An-Li; Ho, Kuan-Ta; Kuo, Ting-Yu; et al.
ABSTRACT: An outbreak of respiratory syncytial virus (RSV) has been observed in Taiwan since August 2020. We reviewed a central laboratory-based surveillance network established over 20 years by Taiwan Centres for Disease Control for respiratory viral pathogens between 2010 and 2020. A retrospective study of children <5 years old hospitalized with RSV infection at Chang Gung Memorial Hospital between 2018 and 2020 was conducted, and samples positive for RSV-A were sequenced. Clinical data were obtained and stratified by genotype and year. Data from 2020 showed an approximately 4-fold surge in RSV cases compared to 2010 in Taiwan, surpassing previous years during which ON1 was prevalent. Phylogenetic analysis of G protein showed that novel ON1 variants were clustered separately from those of 2018 and 2019 seasons and ON1 reference strains. The variant G protein carried six amino acid changes that emerged gradually in 2019; high consistency was observed in 2020. A unique substitution, E257K, was observed in 2020 exclusively. The F protein of the variant carried T12I and H514N substitutions, which weren't at antigenic sites. In terms of multivariate analysis, age (OR: 0.97; 95% CI: 0.94–0.99; p = 0.02) and 2020 ON1 variant (OR:2.52; 95% CI:1.13–5.63; p = 0.025) were independently associated with oxygen saturation <94% during hospitalization. The 2020 ON1 variant didn't show higher replication or virulence compared with those in 2018 in our study. The unprecedented 2020 RSV epidemic may attribute to antigenic changes and lack of interferon-stimulated immunity induced by seasonal circulating virus under non-pharmaceutical intervention.